Fractal-like kinetics of the solid-state anaerobic digestion. (July 2016) - Wang, Zhi-Wu; Xu, Fuqing; Manchala, Karthik R.; Sun, Yewei; Li, Yebo
Highlights: Increase of total solid (TS) content reduced methane production efficiency. Fractal theory was first time applied for solid-state anaerobic digestion (SS-AD). SS-AD reaction followed surface reactions and fractal kinetics. Diffusion in SS-AD is dimensionally restricted by crowded and heterogeneous media. A parameter h was used to describe the fractal characteristics of SS-AD. Abstract: Total solid content (TS) negatively impacts the methane production efficiency (MPE) of solid-state anaerobic digestion (SS-AD), to which the classic mass action-based kinetics failed to provide a unified explanation. This study revealed that SS-AD reactions actually follow the fractal-like kinetics in light of the surface reactions in crowded SS-AD environment packed with heterogeneous media. The fractal characteristics of the SS-AD kinetics were found increasingly pronounced as TS increased. This study represents the first attempt to resolve the dilemma in SS-AD kinetics with the application of fractal theory. Employing this new concept allows explaining the reduced MPE at high TS and offers an easy assessment of the fractal characteristics of the SS-AD media.